Tuberculosis, COVID-19 and migrants: Preliminary analysis of deaths occurring in 69 patients from two cohorts - Motta, I.; Centis, R.; D’Ambrosio, L.; García-García, J.-M.; Goletti, D.; Gualano, G.; Lipani, F.; Palmieri, F.; Sánchez-Montalvá, A.; Pontali, E.; Sotgiu, G.; Spanevello, A.; et al. (Pediatric pulmonology, 2020)
Little is known about the relationship between the COVID-19 and tuberculosis (TB). The aim of this study is to describe a group of patients who died with TB (active disease or sequelae) and COVID-19 in two cohorts. Data from 49 consecutive cases in 8 countries (cohort A) and 20 hospitalised patients with TB and COVID-19 (cohort B) were analysed and patients who died were described. Demographic and clinical variables were retrospectively collected, including co-morbidities and risk factors for TB and COVID-19 mortality. Overall, 8 out of 69 (11.6%) patients died, 7 from cohort A (14.3%) and one from cohort B (5%). Out of 69 patients 43 were migrants, 26/49 (53.1%) in cohort A and 17/20 (85.0%) in cohort B. Migrants: (1) were younger than natives; in cohort A the median (IQR) age was 40 (27–49) VS. 66 (46–70) years, whereas in cohort B 37 (27–46) VS. 48 (47–60) years; (2) had a lower mortality rate than natives (1/43, 2.3% versus 7/26, 26.9%; p-value: 0.002); (3) had fewer co-morbidities than natives (23/43, 53.5% versus 5/26–19.2%) natives; p-value: 0.005). The study findings show that: (1) mortality is likely to occur in elderly patients with co-morbidities; (2) TB might not be a major determinant of mortality and (3) migrants had lower mortality, probably because of their younger age and lower number of co-morbidities. However, in settings where advanced forms of TB frequently occur and are caused by drug-resistant strains of M. tuberculosis, higher mortality rates can be expected in young individuals.